Pediatric Endocrinology A Practical Clinical Guide, Second Edition - Radovick, Sally; MacGillivray, Margaret H. (Contemporary Endocrinology, 2013)
A state-of-the-art and concise guide to the clinical management of pediatric endocrine disorders, the second edition of the highly regarded Pediatric Endocrinology: A Practical Clinical Guide covers the most common and challenging conditions seen by practicing endocrinologists and primary care physicians, including growth, hypothalamic, pituitary, adrenal, thyroid, calcium and bone, and reproductive disorders, as well as metabolic syndromes. This expanded second edition includes new topics being seen more commonly in pediatric endocrinology practices related to obesity and type 2 diabetes mellitus and lipid disorders. Each chapter contains an introductory discussion of the problem, a review of the clinical features that characterize it, the criteria needed to establish a diagnosis, and a comprehensive therapy section delineating the risks and benefits of the best therapeutic options available. Invaluable tables summarize the critical factors in etiology, clinical presentation, diagnosis, and therapeutic dosages.  Pediatric Endocrinology: A Practical Clinical Guide, Second Edition, is a comprehensive resource for all clinicians concerned with the myriad endocrinologic disorders seen in children and adolescents.